Microplastic Pollution in Wastewater Sea Discharge and Deep Sea Discharge Stations into the Marmara Sea and the Bosphorus - Karacam, Seren; Takatas, Betul; Turan, Nouha Bakaraki; Erkan, Hanife Sari; Engin, Guleda Onkal (Mehmet Sinan Bilgili, 2022)
In this study, the abundance, type, size and color of microplastics (MPs) in 17 treated municipal wastewater sea discharge (SD) and deep sea discharge (DSD) stations discharging to the Marmara Sea were investigated. Sea surface water samples were collected to determine MPs abundance and their characteristics at these selected stations. According to the results obtained, the spatial distribution of MPs in SD and DSD stations was determined. Higher MP abundance was detected at the DSD stations where municipal wastewater generally is discharged after pre-treatment, compared to the SD stations where advanced biological wastewater treatment is mainly applied to municipal wastewater. While the highest MP content was found in SD-10 station (Silivri-Canta sea discharge: 770.050,00 MP/km2) for sea surface samples, DSD-4 (Kucuksu Deep Sea Discharge: 1.602.230,00 MP/km(2)) and DSD-2 (Kadikoy Deep Sea Discharge: 1.482.340,00 MP/km(2)) were the stations where the highest MPs were observed in all studied stations.
Keywords: Microplastics; Marmara Sea; Bosphorus; municipal wastewater sea discharge; MARINE-ENVIRONMENT; FATE; INGESTION; IDENTIFICATION; CONTAMINATION; PARTICLES; ABUNDANCE; SEDIMENTS; FISH; BAY; Engineering; Environmental Sciences & Ecology